Modes of Representing the Holocaust: a Discussion of the Use of Animation in Art Spiegelman's Maus and Oryl Yadin and Sylvie Bringas's Silence - Jessica Copley (Opticon1826, 2010)
Since Theodor Adorno’s famous dictum that ‘to write poetry after Auschwitz is barbaric’, the issue of whether it is ethical to represent the Holocaust in art, and if so, the means by which it is ethical to do so, has constituted one of the major polemical discourses of our time. Prominent questions such as ‘Who has the right to try and represent the Holocaust?’, ‘How should we represent the Holocaust?’ and ‘How can we address the issue of responsibility in a post-war world?’ have motivated artistic representations and the critics who discuss these representations. In this essay, I aim to consider the success of two works which employ the somewhat controversial format of animation in dealing with aspects of testimony, trauma, language and responsibility. The first, Art Spiegelman’s 1984 comic book strip Maus, anthropomorphised Germans into cats and Jews into mice in order to narrate events experienced by Spiegelman’s father, Vladek, during the war and the postbellum father-son relationship. Although Maus was initially criticised for its use of the comic book format, traditionally viewed as adolescent, it later went on to receive the Pulitzer Prize for its literary success and as such provided a benchmark for the potential of animated formats. The second, Orly Yadin and Sylvie Bringas’s 1998 animated short film Silence, combines two styles of animation and a small amount of archival footage to tell the story of Tana Ross, a child survivor of Theresienstadt (Terezin) who, hidden by her grandmother during the war, escaped Auschwitz.
Keywords: humour; horror; Holocaust; animation